High-stakes decisions do not require narrative conviction but narrative flexibility. (8th May 2023) - Breithaupt, Fritz; Hicks, Milo; Hiskes, Benjamin; Lagrange, Victoria
Abstract: We challenge Johnson et al.'s assumption that people reduce unclear situations to a single narrative explanation and that such reduction would be adaptive for decision-making under radical uncertainty. Instead, we argue that people imagine and maintain multiple narrative possibilities throughout the decision-making process and that this process provides cognitive flexibility and adaptive benefits within the proposed model.